(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
How does a person perceive forced self-isolation in general and himself in this situation in particular? The target audience was predominantly Russian-speaking residents of France. The conducted study allowed us to see more carefully the ways of living the conditions of forced self-isolation, to discover the general and individual characteristics of changes in various spheres of being of the survey participants. The results of the study may be used for a deeper study of the phenomenon of self-isolation. They can also become the part of a large-scale scientific work in the field of theory and practice of existential psychology.